A robust and reproducible human pluripotent stem cell derived model of neurite outgrowth in a three-dimensional culture system and its application to study neurite inhibition. (June 2017) - Clarke, Kirsty E.; Tams, Daniel M.; Henderson, Andrew P.; Roger, Mathilde F.; Whiting, Andrew; Przyborski, Stefan A.
Abstract: The inability of neurites to grow and restore neural connections is common to many neurological disorders, including trauma to the central nervous system and neurodegenerative diseases. Therefore, there is need for a robust and reproducible model of neurite outgrowth, to provide a tool to study the molecular mechanisms that underpin the process of neurite inhibition and to screen molecules that may be able to overcome such inhibition. In this study a novel in vitro pluripotent stem cell based model of human neuritogenesis was developed. This was achieved by incorporating additional technologies, notably a stable synthetic inducer of neural differentiation, and the application of three-dimensional (3D) cell culture techniques. We have evaluated the use of photostable, synthetic retinoid molecules to promote neural differentiation and found that 0.01 μM EC23 was the optimal concentration to promote differentiation and neurite outgrowth from human pluripotent stem cells within our model. We have also developed a methodology to enable quick and accurate quantification of neurite outgrowth derived from such a model. Furthermore, we have obtained significant neurite outgrowth within a 3D culture system enhancing the level of neuritogenesis observed and providing a more physiological microenvironment to investigate the molecular mechanisms that underpin neurite outgrowth and inhibition within the nervous system. We have demonstrated a potential application of our model in co-culture with glioma cells, to recapitulate aspects of the process of neurite inhibition that may also occur in the injured spinal cord. We propose that such a system that can be utilised to investigate the molecular mechanisms that underpin neurite inhibition mediated via glial and neuron interactions. Graphical abstract: Highlights: Development of a robust, novel neurite outgrowth assay from human pluripotent stem cell derived neural cell aggregates. Synthetic retinoids induce neural differentiation of pluripotent stem cells to a greater extent than natural ATRA. Neurospheres cultured on a 3D scaffold provide a more physiologically relevant model of neurite outgrowth. Suppression of neurite outgrowth by glioma cells in 3D enables the study of neurite inhibitory mechanisms in the glial scar.